Stolen spirits [videorecording (DVD)] - Worthington, Anne (EPF Media, 2023)
In 2021, in the small rural town of Genoa Nebraska, a harrowing search commenced to locate the graves of Native American children who were taken from their tribes and sent to the Genoa U.S. Indian Industrial School, one of America's largest and longest-running boarding schools for indigenous children. The Genoa school was part of a vast network of institutions for Native American children set up in the 19th and 20th centuries across the USA. Their purpose was to assimilate indigenous children into the white man's world. Many of these children left the school their culture broken, some didn't return home at all. Last year, the discovery of more than a thousand graves of children at the sites of former boarding schools in Canada pushed the USA to examine its history. Stolen Spirits is a powerful and haunting story of one community's attempts to uncover the truth about a painful past.